Microstructural Studies on Cryogenically treated High Carbon High Chromium D3 Cold work tool steel used in hole piercing operation on Chain component - K S, SEKAR (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In sheet metal stamping operations like Blanking and Piercing the punches are more prone to failure than the dies. The wear on the punches will affect the size and shape of the components produced. Hence industries are striving to innovate the ways by which the punch life can be prolonged which results in reduced punch changeover time and reduced spending on punch costs. In this study, the effect of cryogenic treatment on the properties of the piercing punches made of High Carbon High Chromium D3 Cold work type tool steels on microstructure, for improvement of tool life has been investigated. Conventionally the tool steel is heat treated by following Stress Relieving, Hardening and Tempering processes. In the present study 4 different groups of punch samples were prepared in High Carbon High Chromium D3 type cold work tool steel. First group of punches were conventional heat treated (HT). The second group of punches are cryogenically treated immediately after Stress relieving and hardening without performing tempering (HC). The third set of punches were cryogenically treated immediately after stress relieving and hardening and finally tempered (HCT) and the last group of punches were conventionally heat treated followed by cryogenic treatment (HTC). The cryogenic treatment is expected to improve the life of punches by improving the properties of the punches. The SEM and OM images of the cryogenically treated punches were taken to assess the improvement in their properties. The results showed significant improvement in properties of cryogenically treated punches favouring improvement in their life.